Plant DNA Extraction Kit – fasTiP-XTM - Ho Wei, Seng; Lai, Pei Sing; Pang Shek, Ling; Ismail, Jusoh (2011)
Plant DNA extraction is prerequisite to any downstream DNA molecular application. However, the conventional DNA extraction from plant tissues are time consuming, tedious and labour intensive which involve liquid nitrogen and hazardous chemicals, such as CIA and phenol-chloroform. In addition, more than half of the DNA would be lost along this process as well. Hence, the development of rapid DNA extraction method, such as fasTiP-X kit, was greatly needed. fasTiP-X kit is a rapid and efficient plant DNA extraction kit which only involves 3 simple steps before PCR amplification. The basic concept of this kit is touch which is transferring plant samples into the extraction buffer; incubate to lyses the plant cells; and finally the solution can be directly use for further analysis. The detailed technical procedure for operating this kit is first by punching the fresh leaf using Harris micro punch®. Then, 6 punched leaf discs are incubated together with 50 μl of Extraction Buffer for 10 minutes in 95°C. After incubation, the incubated solution is mixed by inverting and tapping. Next, 120 μl of Dilution Buffer is added to the incubated solution. Eventually, the mixture can be directly used for PCR amplification. The overall process for the preparation of DNA for PCR amplification using fasTiP-X Kit can be completed in 20 minutes. Besides, it uses small amount (about 5mm2) of samples which reduces the lost of sample to minimal. This kit is applicable in forestry forensic analysis, genetic diversity study and species and clone identification.